1998
DOI: 10.1002/ana.410440231
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E genotypes and age at onset of Parkinson's disease

Abstract: We read with interest the article by Zareparsi and colleagues.' The authors analyzed the influence of the apolipoprotein E (ApoE) ~4 allele on the age at onset of Parkin-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Other contributors may be differences in ethnic origin, proportion of familial cases and other differences between sites. The majority of the subjects in this study were of Northern European origin, whereas the subjects in two studies were Spanish [de la Fuente-Fernandez et al, 1998] and Italian [Oliveri et al, 1999]. It is possible that the effect of APOE on onset of PD differs among ethnic groups, just as the effect of APOE on AD differs among ethnic groups [Farrer et al, 1997].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Other contributors may be differences in ethnic origin, proportion of familial cases and other differences between sites. The majority of the subjects in this study were of Northern European origin, whereas the subjects in two studies were Spanish [de la Fuente-Fernandez et al, 1998] and Italian [Oliveri et al, 1999]. It is possible that the effect of APOE on onset of PD differs among ethnic groups, just as the effect of APOE on AD differs among ethnic groups [Farrer et al, 1997].…”
Section: Discussionmentioning
confidence: 86%
“…Subsequently, four studies have examined the effect of APOE alleles on age at onset of PD. One study found a non-signi®cant 1.6 year earlier onset in e4-carriers ], whereas three studies did not detect an earlier onset in e4-carriers [de la Fuente-Fernandez et al, 1998;Oliveri et al, 1999;Maraganore et al, 2000]. Interestingly, one study found evidence for signi®cantly earlier age at onset in e2e3 patients compared to e3e3 patients [Maraganore et al, 2000].…”
Section: Introductionmentioning
confidence: 90%
“…Interestingly, in the cohort by Zareparsi et al [2002], 29% of the patients had positive FH, while the proportion of patients with positive FH was 12% and 15% in two of the previous studies [Inzelberg et al, 1998;de la Fuente-Fernandez et al, 1998]. In addition, the authors excluded patients whose age of onset was 30 or less, to avoid the inclusion of patients with parkin mutations.…”
mentioning
confidence: 98%
“…One of these studies, by de la Fuente-Fernandez et al [1998], found in fact, paradoxically, significantly older ages of PD onset in e4 carriers. Because all studies [de la Fuente-Fernandez et al, 1998;Inzelberg et al, 1998;Oliveri et al, 1999] cited in Table IV of Zareparsi et al [2002] tested the same hypothesis concerning the effect of ApoE genotype on the age of onset, their combined P value could be calculated using Fisher's inverse w 2 method of combined independent tests on the same hypothesis [Hedges and Olkin, 1985]. The P value for the combination of the additional studies cited in Table IV was 0.598, thus ages of onset were not significantly different among e4 carriers and those who were not.…”
mentioning
confidence: 99%
“…12 Thus far, ApoE analyses in PD, however, have remained contradictory. [13][14][15][16][17][18] Here, we studied several polymorphisms of the ␣-SYN gene locus and the ApoE gene independently and in a combined analysis to define susceptibility genotypes for PD.…”
mentioning
confidence: 99%